Intrinsic and Extrinsic Mechanisms of Thalamic Pathology in Multiple Sclerosis. Issue 1 (1st May 2020) - Mahajan, Kedar R.; Nakamura, Kunio; Cohen, Jeffrey A.; Trapp, Bruce D.; Ontaneda, Daniel
Abstract : Objective: Thalamic atrophy is among the earliest brain changes detected in patients with multiple sclerosis (MS) and the degree of thalamic atrophy is a strong predictor of disability progression. The causes of thalamic atrophy are not fully understood. Here, we investigate the contributions of thalamic demyelinated lesions, thalamic neuronal loss, and cerebral white matter (WM) lesions to thalamic volume. Methods: We used postmortem in situ magnetic resonance imaging (MRI) scans of 95 subjects with MS to correlate thalamic lesion volumes with global MRI metrics. We histologically characterized thalamic demyelination patterns and compared neuronal loss and neuritic pathology in the thalami with the extremes of volume. Results: Grossly apparent thalamic discolorations in cm‐thick brain slices were T2/fluid‐attenuated inversion recovery (FLAIR) hyperintense, T1‐hypointense, and appeared as perivascular demyelinated lesions with dystrophic neurons/axons. Subependymal demyelinated lesions with axonal loss and microglial/macrophage activation were also observed. The 12 subjects with the least thalamic volume had a 17.6% reduction of median neuronal density in the dorsomedial/ventrolateral and pulvinar nuclei compared with the 14 subjects with the greatest thalamic volume ( p = 0.03). After correcting for age, disease duration, sex, and T2 lesion volume, the total ( p = 0.20), ovoid ( p = 0.31), or subependymal ( p = 0.44) MRI thalamic lesion volumes correlated with thalamic volume. Thalamic volume correlated with cerebral T2 lesion volume (Spearman's rho = −0.65, p < 0.001; p < 0.0001 after correcting for age, disease duration, and sex). Interpretation: Our findings suggest the degeneration of efferent/afferent thalamic projections and/or a neurodegenerative process as greater contributors to thalamic atrophy than thalamic demyelinating lesions. ANN NEUROL 2020 ANN NEUROL 2020;88:81–92